Monsoon [+ other] Airs - Bremner, Lindsay; Trower, Georgia (Monsoon Assemblages, 2017)
Monsoon Assemblages is a research project funded by the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (Grant Agreement No. 697873). Monsoon [+ other] Airs is the first of three publications by Monsoon Assemblages arising from symposia held at the University of Westminster (2017-2019). These form part of its agenda to foster interdisciplinary conversations between the environmental humanities (anthropology, environmental studies, political ecology, cultural geography and philosophy), the natural sciences (meteorology, climatology and climate science) and spatial design (architecture, landscape architecture, planning and urban design) to further understandings of the impacts of changing monsoon climates and rapid urbanisation in South Asian cities, and investigate their consequences for the environmental humanities and spatial design practice.